Interactions between network operators, content producers and internet intermediaries: Empirical implications of network neutrality - Antonin Arlandis; Edmond Baranes (Intereconomics, 2011)
Economically the net neutrality debate focuses on the question whether services of different quality should be subject to price discrimination. The debate strongly affects the interaction between the players that are involved in the provision of online content. The authors analyse this interaction and find important synergies between suppliers along the value chain. The revenues of all players depend on investment in networks which determines the quality of content. The benefits of policies that support net neutrality are unequally distributed among the different players. This might explain diverging policy approaches in the USA and Europe.
Keywords: 330